2004
DOI: 10.1523/jneurosci.3009-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Precise Localization of α7 Nicotinic Acetylcholine Receptors on Glutamatergic Axon Terminals in the Rat Ventral Tegmental Area

Abstract: ␣7 neuronal nicotinic acetylcholine receptors (nAChRs) constitute one of the predominant nAChR subtypes in the mammalian brain. Within the ventral tegmental area (VTA), nicotine application, paired with postsynaptic stimulation, contributes to a form of long-term potentiation, an effect attributed to presynaptic ␣7 nAChRs on glutamatergic afferents (Mansvelder and McGehee, 2000). The aim of this study was to examine the precise subcellular distribution of ␣7 nAChRs in the adult rat VTA to establish whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
215
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(223 citation statements)
references
References 43 publications
6
215
1
1
Order By: Relevance
“…In this respect, additional experiments aimed at describing the effect of continuous superfusion of SSR180711 with transient application of ACh or choline at a7 n-AChR would be necessary to better assess the desensitizing properties of the compound. However, exogenous agonists such as SSR180711 may also act as extrasynaptic a7 n-AChRs, shown to be predominant in some neural structures, suggesting that an exogenous agonist could be active without competing against synaptically released ACh ( Jones and Wonnacott, 2004;Coggan et al, 2005). At a more integrated levels and as mentioned in the Introduction section, it is still unclear whether the excitatory effects of a7 n-AChR agonists described in the hippocampus do involve an activation of glutamate release (via activation of a7 n-AChRs) or a decrease of GABA release (by desensitization of a7 n-AChRs) (Fujii et al, 2000;Gray et al, 1996;Hunter et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, additional experiments aimed at describing the effect of continuous superfusion of SSR180711 with transient application of ACh or choline at a7 n-AChR would be necessary to better assess the desensitizing properties of the compound. However, exogenous agonists such as SSR180711 may also act as extrasynaptic a7 n-AChRs, shown to be predominant in some neural structures, suggesting that an exogenous agonist could be active without competing against synaptically released ACh ( Jones and Wonnacott, 2004;Coggan et al, 2005). At a more integrated levels and as mentioned in the Introduction section, it is still unclear whether the excitatory effects of a7 n-AChR agonists described in the hippocampus do involve an activation of glutamate release (via activation of a7 n-AChRs) or a decrease of GABA release (by desensitization of a7 n-AChRs) (Fujii et al, 2000;Gray et al, 1996;Hunter et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…They are located presynaptically on nerve terminals and postsynaptically on dendritic spines and soma, where they modulate neurotransmitter release and are responsible for direct fast excitatory transmission, respectively (Fabian-Fine et al, 2001;Marchi et al, 2002;Alkondon et al, 2000;Frazier et al, 1998). More recently, in two different neuronal preparations, a7 n-AChRs have been shown to be preferentially located at extrasynaptic site, activated by the spillover of ACh released at the active site (Jones and Wonnacott, 2004;Coggan et al, 2005). A large number of studies have demonstrated that a7 n-AChR stimulation can increase both glutamate and GABA release in a number of brain structures, including the hippocampus (Gray et al, 1996;Radcliffe et al, 1999;Reno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is supported by our previous demonstration that local administration of MLA in the VTA reduces food-induced dopamine release in the nucleus accumbens (Schilström et al, 1998b). Moreover, a recent anatomical study demonstrated that a7 nAChRs in the VTA may be located presynaptically at sites indicative of a paracrine mode of signaling (Jones and Wonnacott, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, acute ethanol can also reduce the postsynaptic effects of NMDA and non-NMDA receptors mediating excitation (see Crews et al, 1996)Fanother change that would reduce excitatory drive and allow greater effectiveness of GABA released by ethanol. As with GABA transmission, a number of presynaptic mechanisms can influence glutamate release (see Brown et al, 2004;Jones and Wonnacott, 2004). Since ethanol increases neurosteroids, another aspect that should receive future attention is the possibility that pregnenolone sulfate may enhance spontaneous glutamate release (see Meyer et al, 2002), while reducing release of GABA (Mtchedlishvili and Kapur, 2003).…”
Section: Ethanol On Excitatory Drivementioning
confidence: 99%